(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article deals with the issue of equality of women and men in the Islamic religion. The role of a woman in marriage, family responsibilities, relations between husband and wife, established rights and obligations regarding marriage and love are also analyzed.